(untitled) (Journal of Advanced Research in Social Sciences, 2021)
Music preference is being influenced by various sociological factors. This study was undertaken to investigate music preferences across five different socio-economic classes in selected urban and suburban areas of Sri Lanka. Ten music tracks representing the correspondent musical genres were selected. The single most preferred and the weighted hedonic mean score for the genres in each class were obtained as upper class: jazz, upper middle class: nature music, middle class: popular instrumental, working class: popular instrumental and poor class: rock. The interaction between socio-economic classes and genres was significant (p<0.05). Compelling associations for folk, jazz, and popular instrumental genres were found with the upper-middle class while the upper class has shown a significant association for popular instrumental music. Despite the socio-economic status, the highest preference and the highest weighted hedonic mean score were recorded with popular instrumental. Thus, understanding music preference behaviour is vital for music education and research.